Kynurenine, Tetrahydrobiopterin, and Cytokine Inflammatory Biomarkers in Individuals Affected by Diabetic Neuropathic Pain - Staats Pires, Ananda; Heng, Benjamin; Tan, Vanessa X.; Latini, Alexandra; Russo, Marc A.; Santarelli, Danielle M.; Bailey, Dominic; Wynne, Katie; O’Brien, Jayden A.; Guillemin, Gilles J.; Austin, Paul J. (Frontiers in Neuroscience, 2020)
Neuropathic pain is a common complication of diabetes with high morbidity and poor treatment outcomes. Accumulating evidence suggests the immune system is involved in the development of diabetic neuropathy, whilst neuro-immune interactions involving the kynurenine (KYN) and tetrahydrobiopterin (BH4) pathways have been linked to neuropathic pain pre-clinically and in several chronic pain conditions. Here, using a multiplex assay, we quantified serum levels of 14 cytokines in 21 participants with type 1 diabetes mellitus, 13 of which were classified as having neuropathic pain. In addition, using high performance liquid chromatography and gas chromatography-mass spectrometry, all major KYN and BH4 pathway metabolites were quantified in serum from the same cohort. Our results show increases in GM-CSF and IL-8, suggesting immune cell involvement. We demonstrated increases in two inflammatory biomarkers: neopterin and the KYN/TRP ratio, a marker of indoleamine 2,3-dioxygenase activity. Moreover, the KYN/TRP ratio positively correlated with pain intensity. Total kynurenine aminotransferase activity was also higher in the diabetic neuropathic pain group, indicating there may be increased production of the KYN metabolite, xanthurenic acid. Overall, this study supports the idea that inflammatory activation of the KYN and BH4 pathways occurs due to elevated inflammatory cytokines, which might be involved in the pathogenesis of neuropathic pain in type 1 diabetes mellitus. Further studies should be carried out to investigate the role of KYN and BH4 pathways, which could strengthen the case for therapeutically targeting them in neuropathic pain conditions.